Unilateral transforaminal lumbar interbody fusion through a modified hemilateral spinous process-splitting approach - Liu, Guanyi; Zou, Xiaodi; Dong, Yanzhao; Alhaskawi, Ahmad; Hu, Lihua; Mao, Lu; Qian, Jun; Ying, Jichong; Abdalbary, Sahar Ahmed; Alenikova, Olga; Ma, Yizhong; Lu, Hui (Frontiers in Neurology, 2023)
Objective To describe unilateral transforaminal lumbar interbody fusion (TLIF) via a modified hemilateral spinous process-splitting (MHSPS) approach and determine its effectiveness. Methods Sixty-five consecutive patients with the lumbar degenerative disease who underwent MHSPS TLIF between August 2020 and July 2021 were retrospectively analyzed. Japanese Orthopedic Association (JOA) score and visual analog scale (VAS) scores for back and leg pain were evaluated before surgery and at the last follow-up. Postoperative paraspinal muscle atrophy was evaluated on axial T2-weighted magnetic resonance imaging. Results Mean JOA score increased from 13.6 ± 3.21 before surgery to 24.72 ± 3.34 at last follow-up (p < 0.001). The mean recovery rate was 68.2% ± 5.68%. Clinical outcome was excellent in 22, good in 35, and fair in 8 patients. The VAS score for low back pain was significantly lower at the last follow-up than before surgery (1.18 ± 0.99 vs. 3.09 ± 1.35; p < 0.001). The VAS score for leg pain was also significantly lower at the last follow-up than before surgery (1.13 ± 0.91 vs. 6.61 ± 1.23; p < 0.001). The mean paraspinal muscle atrophy rate did not significantly differ between the symptomatic side (6% ± 3.8%) and asymptomatic side (4.8% ± 3.3%) at last follow -up (p = 0.071). Conclusion MHSPS TLIF is an effective minimally invasive surgical treatment for selected types of degenerative lumbar disease. This technique can achieve effective spinal decompression and interbody fusion. Its advantages include direct and adequate visualization, vast surgical working space, short operation time, and minimal muscle injury.